Stereoselective Total Syntheses of Solifenacin and N-Acetyl-1-(4-chlorophenyl)-6,7-dimethoxytetrahydroisoquinoline - Babu, R. Anji; Reddy, N. Siva Senkar; Reddy, B. Jagan Mohan; Reddy, B. V. Subba (Synthesis, 2014)
A highly stereoselective synthesis of 1-aryl-1,2,3,4-tetrahydroisoquinoline drugs such as solefinacin (muscarinic acetylcholine receptor antagonist) and N-acetyl-1-(4-chlorophenyl)-6,7-dimethoxytetrahydroisoquinoline (AMPA receptor antagonist) has been accomplished using (R)-tert-butanesulfinamide as a chiral source. Chiral tetrahydroisoquinolines have been prepared through the aryl Grignard addition to chiral N-sulfinylimines followed by haloamide cyclization.
Keywords: chiral N-sulfinylimine; aryl Grignard reagent; tetrahydroisoquinoline; 3-hydroxyquinuclidine